Schiff's Bases and Crown Ethers as Supramolecular Sensing Materials in the Construction of Potentiometric Membrane Sensors - Faridbod, Farnoush (Molecular Diversity Preservation International (MDPI), 2008)
Ionophore incorporated PVC membrane sensors are well-established analytical tools routinely used for the selective and direct measurement of a wide variety of different ions in complex biological and environmental samples. Potentiometric sensors have some outstanding advantages including simple design and operation, wide linear dynamic range, relatively fast response and rational selectivity. The vital component of such plasticized PVC members is the ionophore involved, defining the selectivity of the electrodes' complex formation. Molecular recognition causes the formation of many different supramolecules. Different types of supramolecules, like calixarenes, cyclodextrins and podands, have been used as a sensing material in the construction of ion selective sensors. Schiff's bases and crown ethers, which feature prominently in supramolecular chemistry, can be used as sensing materials in the construction of potentiometric ion selective electrodes. Up to now, more than 200 potentiometric membrane sensors for cations and anions based on Schiff's bases and crown ethers have been reported. In this review cation binding and anion complexes will be described. Liquid membrane sensors based on Schiff's bases and crown ethers will then be discussed.